American foundations: roles and contributions - Anheier, Helmut K.; Hammack, David C. (Brookings Institution Press, 2010)
"Assesses comprehensively the impact and significance of philanthropic foundations in the United States and their effect on American culture and society covering areas such as education and research, health care, social welfare, arts and culture, religion, social movements, and international affairs"--Provided by publisher
Includes bibliographical references (p. 409-436) and index
Erscheinungsjahr in Vorlageform:c2010
Keywords: Aufsatzsammlung; Geschichte 1867-2010; Stiftung; USA